Going batty - Klein, Abby; McKinley, John 1956- (New York : Scholastic, 2010)
It's almost Halloween and Freddy thinks that there are monsters in his attic.
P
620
P
Keywords: Fear -- Juvenile fiction; Monsters -- Juvenile fiction; Bats -- Juvenile fiction; Halloween -- Juvenile fiction